2022
DOI: 10.1007/s00402-022-04504-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and treatment of intracapsular femoral neck fractures in Germany

Abstract: Introduction Intracapsular femoral neck fractures are one of the most common fractures in Germany. Nevertheless, the epidemiology and treatment modalities are not described comprehensively. For this reason, this study highlights the epidemiology of femoral neck fractures in different age groups and summarizes treatment strategies within the period from 2009 to 2019 based on nationwide data. Materials and methods In this retrospective cohort study all cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…Geographical differences are also noticeable in this context, with mainly cemented HA being used in Europe, whereas mainly uncemented HA are used in the USA. [ 3 , 31 ]. Several studies reported an increased in-patient mortality for cemented joint replacement surgeries and demonstrated an increased mortality for cemented HA with an odds ratio of 1.64 (95% CI 1.35–2.00) within the first 48 h after surgery [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Geographical differences are also noticeable in this context, with mainly cemented HA being used in Europe, whereas mainly uncemented HA are used in the USA. [ 3 , 31 ]. Several studies reported an increased in-patient mortality for cemented joint replacement surgeries and demonstrated an increased mortality for cemented HA with an odds ratio of 1.64 (95% CI 1.35–2.00) within the first 48 h after surgery [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the femoral neck (FNF) are among the most common fractures in the German population, with an annual number of over 81,000 fractures and an incidence of 120.2 per 100,000 inhabitants. Both an increase of 23% between 2009 and 2019 and a high incidence in the population over 70 years of age (508.2 fractures per 100,000 population/year) underline the relevance of these fractures for the health care system [ 1 3 ]. The increasingly aging society in Germany and the higher prevalence of osteoporosis in old age depict two driving factors of the increasing prevalence of this fracture type [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of intracapsular neck of femur (NOF) fractures continues to rise worldwide [1]. Total hip replacement (THR) is recommended for patients who are independently mobile, have no cognitive impairment, and are fit for anaesthesia.…”
Section: Introductionmentioning
confidence: 99%